2016
DOI: 10.1158/0008-5472.can-15-1591
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Promote the Development and Progression of Liver Metastases after Surgical Stress

Abstract: Risks of tumor recurrence after surgical resection have been known for decades, but the mechanisms underlying treatment failures remain poorly understood. Neutrophils, first-line responders after surgical stress, may play an important role in linking inflammation to cancer progression. In response to stress, neutrophils can expel their protein-studded chromatin to form local snares known as neutrophil extracellular traps (NET). In this study, we asked whether as a result of its ability to ensnare moving cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
572
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 524 publications
(636 citation statements)
references
References 46 publications
15
572
3
4
Order By: Relevance
“…Recently, Tohme et al showed that NETs promote the development and progression of liver metastases after surgical stress. Importantly, in growing metastatic tumors, the authors found that intratumoral hypoxia accentuated NET formation (53). In line of this study, Alfaro et al (54) demonstrated that tumor-produced IL-8 leads to extrusion of NETs in human myeloid-derived suppressor cells, which are considered an important T-cell immunosuppressive component in cancer-bearing hosts (54).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Tohme et al showed that NETs promote the development and progression of liver metastases after surgical stress. Importantly, in growing metastatic tumors, the authors found that intratumoral hypoxia accentuated NET formation (53). In line of this study, Alfaro et al (54) demonstrated that tumor-produced IL-8 leads to extrusion of NETs in human myeloid-derived suppressor cells, which are considered an important T-cell immunosuppressive component in cancer-bearing hosts (54).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils also produce unique structures called neutrophil extracellular traps (NETs) which are composed of extruded DNA and antimicrobial proteins. After surgical stress or infection, cancer cells have been shown to become trapped in NETs which formed in liver and lung capillaries promoting the development of micrometastasis (30, 31). On the other hand, cancer cells were also shown to recruit neutrophils through CXCL15 or HMGB1 secretion (32).…”
Section: Regulation Of Emt By Immune Microenvironmentsmentioning
confidence: 99%
“…The delayed second peak may relate to the formation of a pre-metastatic niche in distant organs with entrapment of circulating tumor cells (CTC) that are released during surgical manipulation. 9–11 These findings are not too surprising, as critically, neural activation and inflammation is clearly associated with the natural history of cancer 12 and biologic plausibility is found in the pathophysiological stress associated with surgery. 13 Surgical tissue damage accompanied by the systemic release of hormones (eg.…”
Section: Introductionmentioning
confidence: 99%
“…45 Neutrophils activated by platelets may also release chromatid DNA into the extracellular environment, with the formation of neutrophil extracellular traps (NET) that likely evolved to trap bacteria and parasites but may also promote adhesion of circulating tumor cells in the sinusoids of metastasis prone distant sites such as the lung and liver. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation